Manajemen Rantai Pasokan, Keunggulan Bersaing, dan Dampaknya terhadap Kinerja Usaha Toko Roti - Hapsari, Paramesthi Wulan; Supriadi, Asep; Ganika, Gerry (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to test, analyze and prove how the mediation role of Competitive Advantage on the relationship between Supply Chain Management and Business Performance studied in bakery businesses in South Jakarta. The type of research used is quantitative descriptive. This study uses data collection methods based on interviews, literature studies and questionnaires. The population in this study is micro, small and medium enterprises (MSMEs) engaged in bread production with a population of 200. The sample used in this study was 134 respondents using purposive sampling techniques. The data analysis technique used is Structural Equation Modeling (SEM) with the Smart PLS 4.2.1.1 analysis tool. The results of this study indicate that: (1) Supply Chain Management has a positive and significant effect on Business Performance, (2) Supply Chain Management has a positive and significant effect on Competitive Advantage, (3) Competitive Advantage has a positive and significant effect on Business Performance and (4) Competitive Advantage is able to mediate the influence of Supply Chain Management on Business Performance.